MUSEUM VISIT INTENTION: THE EFFECT OF SOCIAL MEDIA MARKETING AND INFLUENCER'S CREDIBILITY - Putri, Catherine Chandra; Tjokrosaputro, Miharni (Graduate Program of Universitas Tarumanagara, 2024)
Social media marketing and influencer credibility are viewed as marketing tools in the destination industry. This study explores the influence of social media marketing and influencer credibility on visit intention at the Moja Museum destination. The study expanded the source credibility theory to the use of social media marketing and influencer credibility on the intention to visit. The respondents obtained in this research were 261 who knew the Moja Museum destination and had watched the social media content of @azizsyafiullah and other influencers regarding Moja Museum. Data collection was obtained from distributing questionnaires via Google Form by using purposive sampling techniques. The measurement of this study used a 5-point Likert scale. Analyses on this study were conducted on 236 valid respondents by using Structural Equation Modeling. Results indicated that social media marketing and influencer credibility significantly positively influence visit intention. The implications of this research state that the increases uses of social media marketing and influencer credibility as a marketing method can influence the intention to visit a destination.